(untitled) (Research, Society and Development, 2020)
The objective is to evaluate fluctuations in rainfall entropies in daily, monthly and annual cycles and in the occurrence of dry and rainy seasons and standard deviations, in the period 1960-2018 in Bom Jesus Piauí. Fault filling, homogenization and consistency of data were performed based on the criteria of analyzing for those continuous series after their filling, the method applied to fill in the data flaws was by the inverse of the squared distance. The daily rain data was provided from the conventional meteorological station of the National Institute of Meteorology. High entropy values were recorded in years with intense rainfall, and low entropy values in years of lower rainfall, caused by their irregularities.